Stage deformation characteristics of natural and saturated crushed gangue with large particle size - LU Wei; LU Yao; LIAO Changlong; LI Qinghai; LI Weiyu; JIANG Ning; MU Wenqiang; WANG Changxiang (矿业科学学报)
This study investigates the deformation characteristics and energy consumption patterns of natural and saturated crushed gangue with large particle size during loading-constant load stage through compression test. The results show that: 1) The deformation of natural and saturated crushed gangue in the loading stage accounts for more than 90% of the total deformation. The load gradient significantly affects the displacement deformation in the early stage, and the water also exerts major influence on the displacement deformation in the creep stage. 2) Under natural and saturated conditions, about 1/3 of the work is consumed by friction, while 2/3 by crushing; 3) Compared with the natural state, energy consumption and its variation rate are reduced in the full stage of saturated crushed gangue. The displacement curve shows an explicit three-stage pattern of sharp deformation, linear deformation and creep deformation. According to the first-order and second-order derivatives of the displacement curve, we proposed the judgment basis of the threestages of sharp-linear-creep deformation. When the deformation of crushed gangue exceeds 15%, we observed improved bearing capacity. By observing the gangue compression process, we found that the crushed gangue shows a more uniform internal force chain distribution in the saturated state, with a higher number of cracks, crack growth rate and secondary crushing rate than those in the natural state. Under natural and saturated conditions, when the top void ratio of crushed gangue exceeds 0.65, we observed the maximum secondary crushing rate, with the bottom void ratio of less than 0.45, as well as the minimum secondary crushing rate, with the middle void ratio remaining stable at about 0.5. The secondary crushing loss and the top sliding retention can offset each other. The present study could provide reference for the design, stability monitoring and prediction of coal gangue filling.